High school teachers' attitudes and reported behaviors towards controversial issues. (February 2018) - Gindi, Shahar; Erlich, Rakefet Ron
Graphical abstract: Highlights: 30% of teachers know the official policy regarding political discussions in class. Teachers who feel supported conduct more discussions of controversial topics. Teachers' who view civic education as part of their role report more discussions. Teachers' self-efficacy predict more discussions in class. Teachers who undergo multicultural training discuss controversial topics more.